Crime, law and justice in New Zealand - Newbold, Greg (Routledge, 2016)
Introduction -- Dishonesty -- Gender -- Sex -- Violence -- Youth and Ethnicity -- Drugs -- Gangs and organised crime -- Corrections and crime control